1999
DOI: 10.1103/physrevb.60.7718
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical effects in photoluminescence of Si nanocrystals

Abstract: We report on magneto-optical studies of excitons confined in Si nanocrystallites. As a result of Zeeman splitting of the exciton ground level the whole resonantly excited photoluminescence spectrum shifts linearly to lower energy with rising magnetic field. The recombination decay time depends on magnetic field due to the change in the thermal populations of singlet-triplet sublevels of the exciton ground state. The effect is stronger for weakly confined excitons when the value of the Zeeman splitting becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…[40,59] Despite the fact that this treatment of the structure of the exciton ground level in Si nanocrystals is simplified, it explains all the experimental observations very well. [60] In Figure 7, the resonant PL spectrum measured very near the excitation energy is shown. The spectral gap D exch , of the order of a few millielectronvolts, between the excitation line and the onset of emission is clearly seen.…”
Section: Spin Structure Of Excitons Confined In Si Nanocrystalsmentioning
confidence: 98%
See 1 more Smart Citation
“…[40,59] Despite the fact that this treatment of the structure of the exciton ground level in Si nanocrystals is simplified, it explains all the experimental observations very well. [60] In Figure 7, the resonant PL spectrum measured very near the excitation energy is shown. The spectral gap D exch , of the order of a few millielectronvolts, between the excitation line and the onset of emission is clearly seen.…”
Section: Spin Structure Of Excitons Confined In Si Nanocrystalsmentioning
confidence: 98%
“…The first experimental evidence for the importance of this type of interaction in Si nanocrystals was provided by Calcott et al [40] and was later confirmed by a number of different groups. [58][59][60] The upper and lower exciton states are assumed to be an optically active spin singlet (S = 0) and an optically passive spin triplet (S = 1), respectively. Although spin-orbit interaction in Si is weak, it has been shown to play an important role in Si nanocrystals.…”
Section: Spin Structure Of Excitons Confined In Si Nanocrystalsmentioning
confidence: 99%
“…At Surprisingly, the most interesting results with also a very clear interpretation have been found from studies of the PL spectral response as a function of external magnetic and electric fields. Following the initial report that an external magnetic field increases the energy gap between singlet and triplet states in Si nanocrystals, the fact that the PL lifetime increases while the intensity decreases in Si nanocrystals with increasing magnetic field was quite well understood [78][79][80]. However, our studies show that in nc-Si superlattices this PL quenching is selective and affects only PL at wavelengths longer than ~ 750 nm.…”
Section: Photoluminescencementioning
confidence: 67%
“…In a silicon nanostructure with another dielectric, they arise as a result of excitation of charge carriers in the silicon nanocrystallites [17]. In an external magnetic field in silicon nanocrystallites of size 2-3 nm, substantial polarization of nuclei for the magnetic isotope of silicon is possible using such states.…”
Section: Introductionmentioning
confidence: 99%